(untitled) (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2016)
The Kamshoka formation in Al-Rasafa basin is the second reservoir , because it has a petroleum importance, where these formation have not petrol in Syria exception in Al-Rasafa basin, where the fracture calk rock , and dolomite contain a good amount of hairdo carbonate, so it gave the importance of. Theaim of these research is to do petro logical, and geneses analyses ofKamshoka formation, and to estimate the storage characters , and define characters , and kinds and porosity of fracture calk rock , and dolomite, and to have conclusion about the conditions, and environments of sedimentation, and the stages of sedimentation development for the all area. The Kamshoka formation showed a good productivity in some holes which was drilled brand-new, and it gives a hopes to new discovering in another areas in Syria . تعد تشكيلة الكامشوكا الخزان النفطي الثاني ضمن حوض الرصافة إذ إن تشكيلة الكامشوكا غير حاملة للنفط في كل سوريا باستثناء حوض الرصافة حيث يحتوي الكلس والكلس المدلمت المشقق فيها على نسبة جيدة من الهيدروكربونات ، ومن هنا تأتي أهمية هذا البحث. يهدف البحث إلى إجراء تحليل بترولوجي منشئي لصخور تشكيلة الكامشوكا, وتقييم خصائصها الخزنية ، وتحديد صفات ونوعية، ومسامية النطاقات الكلسية ، والكلسية المدلمتة، والمشققة، واستنتاج الشروط السائدة والبيئات الملائمة للترسيب , وكذلك مراحل التطور الترسيبي لكامل منطقة الدراسة . كما أن تشكيلة الكامشوكا تبدي إنتاجية جيدة في بعض الآبار المحفورة حديثاً وتعطي بوادر أمل على اكتشافات أخرى في مناطق أخرى من سورية .